Of Ideas and Objects - Gendreau, Andrée (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2012)
This article provides a comparative overview of the history of museums in Europe and North America, from their origins to their most recent postmodern transformations. It highlights the very unique evolution of museums in North America compared to their European counterparts due to their emphasis on leisure and their strong ties with local communities. It also shows how museums in Quebec, and in Canada as a whole, tend to focus more on ideas than those in Europe, the Musée de la civilisation being a prime example. North American museums have demonstrated the capacity to adapt to the specific needs of communities by being open and flexible institutions capable of preserving heritage, speaking to citizens, and transmitting − or simply bringing life to − past and present cultures.